Persepsi Dan Pengalaman Dokter Terhadap Notifikasi SIMRS Untuk Meningkatkan Kepatuhan Pengisian Rekam Medis Rumah Sakit - I Wayan Nova Suandita (Universitas Ivet, 2026)
Failure to complete medical records within the 24-hour mandate due to excessive clinical workloads poses significant risks to patient safety and triggers operational inefficiencies within hospitals. This issue is often linked to suboptimal physician perceptions regarding the integration of automated notification features in Hospital Management Information Systems (HMIS) as a strategic intervention for enhancing documentation discipline. This study aims to evaluate physician perceptions toward the utilization of HMIS notification applications for medical record completion. A literature review was conducted employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Research findings indicate that the implementation of automated notification features within Hospital Information Management Systems (HIMS) effectively enhances medical documentation compliance and service efficiency; however, its success is heavily contingent upon physicians' perceptions of system ease of use and usefulness, aligned with the Technology Acceptance Model (TAM). An intuitive and precise user experience is essential for ensuring that this technology is embraced as a practical clinical workflow solution rather than a cognitive burden or administrative barrier, provided it is meticulously designed to mitigate alert fatigue.